EFEKTIVITAS GEL EKSTRAK KASAR BROMELIN KULIT NANAS (Ananus comosus L. Merr) HASIL OPTIMASI FORMULA PADA TIKUS YANG DIBUAT LUKA MEMAR - Anang Setyo Wiyono; Dian Mustofani (Fakultas Farmasi UMI, 2019)
Pineapple (Ananus comosus L. Merr) peel contains a protease enzyme, it was called bromelain. The purpose of this study was to develop a crude extract of bromelain of pineapple peel to be formulated into a gel and to determine the effects of crude extract of bromelain of pineapple peel gel on injury healing of rats skin contusion. Fresh pineapple peel carried out in order to get a crude extract of bromelain using the Herdyastuti’s method (2006) then formulated into a gel preparations with variations in the concentration of gelling agent and humectant. The evaluation of the quality of gel preparations were carried out, which included organoleptic test, homogeneity test, dispersion test, pH test, and viscosity test. The results of the evaluation of the quality of gel preparations were optimized using Simplex Lattice Design (SLD) to applied into 3 (three) dosage variations of the crude extract of bromelain of pineapple peel, namely 150 mg / KgBB, 300 mg / KgBB, and 450 mg / KgBB. The results showed that there was an effect of the concentration of carbopol 940 and glycerin on the organoleptic test, dispersion test, pH test and viscosity test, and there was no effect of the concentration of carbopol 940 and glycerin on homogeneity tests. The 3 (three) dosage variations of the optimum gel formula have healing activity on rats skin contusion.